A multiagent system to assist elder people by TV communication - Parra, Víctor; López, Vivian; Mohamad, Mohd Saberi (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2014)
This paper presents a model that assist seniors requiring care. This system is based on a multiagent platform in order to facilitate the communication of the modules composing the model. The application allows independence for the elderly, as he is moving in a secure environment. Besides, it provides different facilities through a platform accessible to everyone, by using the TV.